Design a Low Power Zigbee based smart energy Metering (International Journal of Engineering and Computer Science, 2017)
The Designing and implementing a system based on wireless communication. This paper presents an implementation methodology for a wireless automatic meter reading system using LabVIEW platform and ZigBee network technology. A system design using low power radio communication which is low cost, high performance, highest data rate, highest coverage area and most appropriate to deal with shortcomings of traditional meter reading system , which are related errors in reading the data , inaccuracy of parameters, and timely availability of data . The system is designed and tested wireless in lab environment against it performance, data payload, and reliability.The system is designed using electric meter, National Instruments software and, and ZigBee module. This system performs tasks creating the wireless network and transmits and receives the command for meter reading. This proposed system had potential to save meter reading cost, and additional enabling the many advance services of electrical utilities. Keywords: ZigBee, GPRS, NI, LabVIEW, Mesh Network